2012
DOI: 10.1152/ajplung.00370.2011
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary microRNA profiling in a mouse model of ventilator-induced lung injury

Abstract: The aim of this study was to investigate the changes induced by high tidal volume ventilation (HVTV) in pulmonary expression of micro-RNAs (miRNAs) and identify potential target genes and corresponding miRNA-gene networks. Using a real-time RT-PCR-based array in RNA samples from lungs of mice subjected to HVTV for 1 or 4 h and control mice, we identified 65 miRNAs whose expression changed more than twofold upon HVTV. An inflammatory and a TGF-β-signaling miRNA-gene network were identified by in silico pathway … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
89
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(92 citation statements)
references
References 50 publications
3
89
0
Order By: Relevance
“…Vaporidi et al 49 demonstrated that ectopic expression of miR-21 reduced lung compliance and increased alveolar-arterial oxygen differences and protein levels in bronchoalveolar lavage in a ventilator-induced mouse ALI model. 49 Here, we observed that treatment with the miR-21 mimic abolished the protective effect of LXA 4 on LPSreduced ENaC-γ expression. In addition, both SR11302 and LXA 4 reversed LPS-decreased ENaC-γ protein expression.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Vaporidi et al 49 demonstrated that ectopic expression of miR-21 reduced lung compliance and increased alveolar-arterial oxygen differences and protein levels in bronchoalveolar lavage in a ventilator-induced mouse ALI model. 49 Here, we observed that treatment with the miR-21 mimic abolished the protective effect of LXA 4 on LPSreduced ENaC-γ expression. In addition, both SR11302 and LXA 4 reversed LPS-decreased ENaC-γ protein expression.…”
Section: Discussionmentioning
confidence: 62%
“…Consistent with previous studies that upregulated miR-21 depressed PTEN mRNA and protein expression in ventilator-induced and OA-stimulated rat ALI model. 47,49 In addition, PTEN contains miR-21-binging site within 3′ UTR. 45 Hence, we provide evidence linking LPS-mediated upregulation of miR-21 with downregulation of PTEN mRNA and protein in alveolar epithelia.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have revealed that miR-155 was involved in the development of inflammatory lung disease (20,21). For example, elevated miR-155 could promote inflammation in the lung in cystic fibrosis disease (22).…”
mentioning
confidence: 99%
“…For example, elevated miR-155 could promote inflammation in the lung in cystic fibrosis disease (22). Global miRNA profile analysis showed that the expression of miR-155 was elevated in ALI (21,23). Furthermore, miR-155 could regulate the transduction of TLRs signaling on mouse and human immune cells such as macrophages (24,25), *Department of Respiratory Medicine, East Hospital, Tongji University School of Medicine, Shanghai, China; which was critical for generation of proinflammatory cytokine storm and subsequently the development and recovery of ALI (26)(27)(28).…”
mentioning
confidence: 99%
“…Zhong et al (2012) and Liu et al (2013) further reported that miRNA-21 increased cell growth, promoted migration and invasion, and enhanced chemo-or radio-resistance of non-small cell lung cancer cells, mainly by acting on the phosphatase and tensin homolog signaling pathway and by down-regulating human mutS homolog 2, one of the core mismatch repair genes. In addi- tion, Vaporidi et al (2012) reported that miRNA-21 could be highly up-regulated by high tidal volume ventilation, and could exert a negative effect on lung compliance through increasing alveolar-arterial oxygen differences and the level of inflammation of the associated protein. Yang et al (2012a) further showed that miRNA-21 plays an important role in the pathogenesis of chronic hypoxia-induced pulmonary vascular remodeling.…”
Section: Differentially Expressed Mirnas Between Bpd and Control Groupsmentioning
confidence: 99%